KEPUASAN PELANGGAN XO TOUR AND TRAVEL DI SURABAYA - Gautama, Gandhi (Universitas Widya Kartika Surabaya, 2024)
In this modern era, the tour and travel business in Indonesia has become very fast due to the enthusiasm of local tourists and tourists who want to vacation efficiently. Xo Tour and Travel is one of the tour and travel business services, this business is interested in almost all groups and is starting to grow rapidly, but over time this business has experienced a reduction because the services and facilities provided by XO Tour and Travel are less than satisfactory. This research aims to determine customer satisfaction using Xo Tour & Travel services and to determine whether the quality of service provided by XO Tour & Travel has an effect on customer satisfaction. This research uses qualitative methods, with data analysis techniques, data collection techniques using interview and questionnaire methods. The results of this research show that the level of consumer satisfaction which consists of the level of loyalty and repeat purchases, the level of customer complaints and the level of recommendations shows many positive responses from customers.